Two new species of Kamimuria (Plecoptera: Perlidae) from Shaanxi Province, China - Li, Weihai; Mo, Raorao (Zootaxa, 2018)
Two new species of the perlid genus Kamimuria Klapálek, K. shaanxinensis sp. nov. and K. yangxiana sp. nov. from Shaanxi Province of northwestern China are described in this paper. The similar characteristics of the new species and related taxa are discussed.